Epidemiology and factors associated with the severity of viral acute lower respiratory infection in children hospitalized in Manaus, Amazonas, in 2017–2018: An observational study. Issue 18 (7th May 2021) - Sobrinho, Fabrícia L.D.V.; Aragon, Davi C.; Carlotti, Ana P.C.P.
Abstract : Abstract: To investigate the epidemiology and factors associated with the severity of viral acute lower respiratory infection (ALRI) in children hospitalized in Manaus, Amazonas, in 2017 to 2018. Retrospective cohort study of children hospitalized at the Hospital and Emergency Room Delphina Rinaldi Abdel Aziz, in Manaus, from April 01, 2017 to August 31, 2018, with a clinical diagnosis of ALRI and nasopharyngeal aspirates positive for at least 1 respiratory virus. One hundred forty-six children aged 0.2 to 66 months (median 7 months) were included. Patients were divided into 2 groups according to the disease severity classified by an adapted Walsh et al score: moderate disease, score 0–4, n = 66 (45.2%) and severe disease, score 5–7, n = 80 (54.8%). A greater number of viral ALRI cases were observed in the rainiest months. Respiratory syncytial virus was the most prevalent (n = 103, 70.3%), followed by metapneumovirus (n = 24, 16.4%), influenza virus (n = 17, 11.6%), parainfluenza virus (n = 11, 7.5%), and adenovirus (n = 4, 2.7%). Co-detections of 2 to 3 viruses were found in 12 (8.2%) patients. The presence of viral coinfection was an independent risk factor for disease severity (adjusted relative risk [RR] 1.53; 95% CI 1.10–2.14). Twelve patients (8.2%) died, all with severe disease. Risk factors for death were shock (adjusted RR 10.09; 95% CI 2.31–43.90) and need for vasoactive drugs (adjusted RR 10.63; 95% CI 2.44–46.31). There was a higher incidence of viral ALRI in Manaus in the rainy season. Respiratory syncytial virus was the most prevalent virus. The presence of viral coinfection was an independent risk factor for disease severity.